Theoretical and Empirical Models of Organizational Learning Processes in Knowledge Management - Frumkina, Aryna (Dr. Viktor Koval, 2023)
Introduction. This study undertakes a comprehensive exploration of existing instructional organizational models, spanning various disciplines within contemporary educational theory and knowledge management practice. The core objective is to propose an all-encompassing model tailored specifically to the preparation of future educational managers. This model places a significant emphasis on integrated educational strategies, further enriched by the integration of organizational learning processes in the context of knowledge management. Aim and tasks. This study critically examines established models of organizational learning processes with the goal of developing a tailored model for training future educational managers. The goal is to equip aspiring educational managers with integrated didactic skills based on analyses of existing educational models that include concept analysis, model evaluation, and theoretical framework establishment. Result. Organizational learning principles drive data-driven refinement, collaborative cross-disciplinary strategies, and leadership development. Sharing best practices enhances strength, whereas iterative feedback processes mitigate its limitations. This dynamic framework encourages adaptable education, fostering continuous improvement in teaching methods, curricula, and managerial training for a sustained educational evolution. Leveraging insights from existing models, the primary aim is to establish an instructional framework that seamlessly integrates a diverse range of content. Notably, the suggested model for training educational managers integrates teaching methodologies, character development, and methodological support for cultivating cultural learning skills, all underpinned by organizational learning processes within the domain of knowledge management. Furthermore, this integrated model incorporates progressive learning objectives that progressively increase in complexity and span the methodologies and resources employed to ensure effective learning outcomes based on comprehensive feature assessment techniques that gauge understanding and competencies. Conclusions. This study navigates the landscape of models, culminating in the proposal of an integrated framework that caters to comprehensive aspiring training. This model facilitates the harmonious amalgamation of various subjects, and proficiencies introduce organizational learning processes within the domain of knowledge management. By fostering a multidisciplinary and holistic approach, this model equips future educators with the multifaceted demands of modern primary education while adequately managing knowledge within their organizational contexts.